The effects of instruction of formulaic sequences and working memory on Malaysian ESL learners’ oral fluency - Maryam Orang; Ghayth Kamel Shaker Al-Shaibani; Thomas Voon Foo Chow; Eng Tek Ong (Penerbit Universiti Kebangsaan Malaysia, 2024)
Despite being exposed to the English language for more than 13 years, Malaysian students have yet to reach the required proficiency level (i.e. appropriate selection and appropriate speech production in general and oral fluency in particular). Many of them experience difficulties at the workplace due to inadequate English skills, particularly in speaking. This study sheds light on the effects of explicit instruction of Formulaic Sequences (FSs) on low-intermediate and intermediate Malaysian ESL learners’ use of formulaic sequences and oral fluency while considering their working memory capacity. A sample of 54 students enrolled in a preparatory English language course was selected through purposive sampling. They were classified as intermediate and low intermediate ESL learners based on their Malaysian University English Test (MUET) results with band scores of 2 and 3, categorized as low-intermediate and intermediate users, respectively.They were divided into two groups: the experimental group (EG) and the control group (CG) by selecting them as similar as possible. The EG received a specific treatment encompassed the explicit instruction of FSs, fluency workshops, and conscious-raising awareness activities, embedded in the regular content materials for fifteen sessions with three-hour-long each session. Both samples were pre-tested and post-tested, followed by semi-structured interviews. In sum, both quantitative and qualitative findings revealed positive effects of explicit instruction of FSs on the participants’ use of FSs and their L2 oral fluency related variables. However, the correlation between the working memory (WM) and participants’ performance did not reach the hypothesized level. The results also supported the proficiency-related and language-dependent features of WM, the general capacity and general processing hypotheses, and the task-specific view. By integrating both communicative and cognitive approaches, this research would benefit the curric